If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-1) = 8 Multiply -1 * -1 y + 1 = 8 Reorder the terms: 1 + y = 8 Solving 1 + y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 8 + -1 Combine like terms: 1 + -1 = 0 0 + y = 8 + -1 y = 8 + -1 Combine like terms: 8 + -1 = 7 y = 7 Simplifying y = 7
| 5y-3=13y+37 | | -5x-6=4x+12 | | 6p^2-10p+6=2 | | 10-5s-3=-s+6 | | 2e-12=7e+8e | | y-(-2)=8 | | -2(1x+6)=-24 | | 119.5299*x=250 | | 45=1-4n | | 0=-15+1x | | 3/10-5s=-s+6 | | 2x+3=86 | | 6a=4b+(8a-3b) | | y-(-3)=8 | | 4v^2+14v+6=0 | | 3+7x=4x-12 | | 9x+7=6x+4 | | 125x+400=900 | | 10x/2 | | 2x+7=22-x | | z/2=10 | | -5(x-4)=7(3-x) | | 1=2(3)+b | | 81=9r | | 2x-3=17-2x | | -5(-1-4)=7(3-(-1)) | | 3-2x+x=15 | | -7*x=1 | | -5/66+(-7)/99 | | 3.5x+5.5(445-x)=1909.5 | | 3(4x-1)+5x=6+4(3+2x) | | 5(x-3)=5(7-4x) |